Skills in Conflict Management & Negotiation in Health Professions - Pedrosa, Vanda Varela (2020)
This presentation Aims to give better understanding of conflict management and negotiation related with health settings, particularly in Primary Health Care. Relevant topic to educate the educators, internationalized learning outcomes: 21st century skills competences, understanding interprofessional teaching, learning & assessment.